Genetic and Genomic Characterization of a New Beef Cattle Composite Breed (Purunã) Developed for Production in Pasture-Based Systems - Mulim, Henrique Alberto; Brito, Luiz F.; Batista Pinto, Luís Fernando; Moletta, José Luis; Da Silva, Lilian Regina; Pedrosa, Victor Breno (Frontiers in Genetics, 2022)
Purunã is a composite beef cattle breed, developed in Southern Brazil through crossing of the Angus, Charolais, Canchim, and Caracu breeds. The goal of this study was to perform the first genetic characterization of the Purunã breed, based on both pedigree and genomic information. For this, 100 randomly-selected animals were genotyped and 11,205 animals born from 1997 to 2019 had pedigree information. The genetic analyses performed were Principal Component Analysis, Admixture, Phylogenic Tree, pedigree and genomic inbreeding, linkage disequilibrium (LD), effective population size (Ne), consistency of gametic phase, runs of homozygosity (ROH), heterozygosity-enriched regions (HER), and functional analyses of the ROH and HER regions identified. Our findings indicate that Purunã is more genetically related to the Charolais, Canchim, and Angus breeds than Caracu or Nellore. The levels of inbreeding were shown to be small based on all the metrics evaluated and ranged from -0.009 to 0.029. A low (-0.12 to 0.31) correlation of the pedigree-based inbreeding compared to all the genomic inbreeding coefficients evaluated was observed. The LD average was 0.031 (±0.0517) and the consistency of gametic phase was shown to be low for all the breed pairs, ranging from 0.42 to 0.27 to the distance of 20 Mb. The Ne based on pedigree and genomic information was 158 and 115, respectively. A total of 1,839 ROHs were found and the majority of them are of small length (<4Mb). An important homozygous region was identified on BTA5 with pathways related to behavioral traits (sensory perception, detection of stimulus, and others), as well as candidate genes related to heat tolerance (MYO1A), feed conversion rate (RDH5), and reproduction (AMDHD1). A total of 1,799 HERs were identified in the Purunã breed with 92.3% of them classified within the 0.5-1Mb length group, and 19 HERs islands were identified in the autosomal genome. These HERs islands harbor genes involved in growth pathways, carcass weight (SDCBP), meat and carcass quality (MT2A), and marbling deposition (CISH). Despite the genetic relationship between Purunã and the founder breeds, a multi-breed genomic evaluation is likely not feasible due to their population structure and low consistency of gametic phase among them.